The effects of different intensities, frequencies and exposure times of extremely low-frequency electromagnetic fields on the growth of Staphylococcus aureus and Escherichia coli O157:H7. (22nd November 2013) - Bayır, Ece; Bilgi, Eyüp; Şendemir-Ürkmez, Aylin; Hameş-Kocabaş, E. Esin
Abstract: The impact of different types of extremely low-frequency electromagnetic fields (ELF-EMF) on the growth of Staphylococcus aureus and Escherichia coli O157:H7 was investigated. The cultures of bacteria in broth media were exposed to sinusoidal homogenous ELF-EMF with 2 and 4 mT magnetic intensities. Each intensity for each bacteria was combined with three different frequencies (20, 40 and 50 Hz), and four different exposure times (1, 2, 4 and 6 h). A cell suspension of each experiment was diluted for the appropriate range and inoculated to Mueller–Hinton Agar (MHA) plates after exposure to ELF-EMF. The number of colony forming units (CFU) of both strains was obtained after incubation at 37 °C for 24 h. Data were statistically evaluated by one-way analysis of variance (ANOVA), statistical significance was described at p  < 0.05 and data were compared with their non-exposed controls. Magnetic intensity, frequency and exposure time of ELF-EMFs changed the characteristic responses for both microorganisms. Samples exposed to ELF-EMF showed a statistically significant decrease compared to their controls in colony forming capability, especially at long exposure times. An exposure to 4 mT–20 Hz ELF-EMF of 6 h produced maximum inhibition of CFU compared to their controls for both microorganisms (95.2% for S. aureus and 85% for E. coli ).